The psychosocial burden of anogenital warts on Syrian patients: study of quality of life. Issue 7 (July 2022) - Haddad, Joud; Hasan, Fouz; Roumeih, Abdel Halim; Omar, Abdullah
Abstract: Purpose: The prevalence of anogenital warts caused by HPV has been on the rise in the war-torn country of Syria recently. Although physically mildly symptomatic, this disease has a considerable negative psychological effect on patients. This study showed up to reveal information on the quality of life (QoL) of these patients and its connection to age, gender, disease severity, educational level and marital status. Methods: The study sample consisted of 57 males and 45 females aged between 18 and 64 years old. The patients were recruited from the main university hospital in Latakia, Syria. The assessment was done using two questionnaires: EQ-5D and CECA10. Results: The data from the EQ-5D revealed no problems in Mobility, Self-care or Usual Activities. Whereas, our study showed extreme levels of anxiety and depression in roughly 50% of the sample. A noticeable impact was seen in 31% of participants describing moderate pain and discomfort. The CECA10 questionnaire revealed an average of disease-specific QoL of 2.48 which indicates a moderate to severe impact. We noticed a statistically significant relationship between the QoL and the patient's age. The age group of 20–29 has suffered the most. Without statistical significance, the psychological burden was at its worst in single patients with severe disease and a high level of education. Females suffered a slightly worse emotional impact compared to males. Conclusion: This study proved a negative effect of genital warts on patients mainly young educated individuals, females and severe cases.